Nordic wage formation and unemployment seven years later - Asbjørn Rødseth; Ragnar Nymoen (University of Oslo, Department of Economics, 1999)
The paper performs a reinvestigation of Nordic wage formation along the lines of Calmfors and Nymoen (1990) with data that include the recent period of high unemployment and low in ation. Among the main findings are: 1)There has been no shift in Nordic wage formation since 1987. 2)The wage formation in Denmark, Finland, Norway and Sweden is fairly similar, even though the unemployment histories differ. 3)Real wage flexibility is not particularly high in the Nordic countries. 4)No strong conclusions can be drawn about the effects of active labour market programs, but an increase in the supply of such programs seems to increase the equilibrium total unemployment rate. 5)Only in Norway is there evidence that incomes policy has been effective. The paper gives some, but limited, support to those who attribute the good employment performance of Norway and Sweden until the late 1980s to aggregate demand factors and devaluations.
Keywords: 330; Lohnbildung; Lohnrigidität; Arbeitsmarktpolitik; Norwegen